Factors Influencing People’s Five Precepts Observance, A Case Study of Pgaz-Koen-Yau Community in Ban Mae Ka Nai, Mae Ho Sub-District, Mae Sariang District, Mae Hong Son Province - Laping, Uten; Chienjuntuk, Sangad; Phoolaiyao, Kittikoon; Kammungkun, Pradit; Wichaiwong, Monthri (Journal of Buddhist Education and Research (JBER), 2015)
The purposes of this research are 1) to study the factors influencing people’s observance of the five precepts 2) to identity the advantages of observing the five precepts and 3) to recommends methods for observing the five precepts for people in Pgaz-koen-yau Community in Ban Mae KaNai, Mae Ho Sub-District, Mae Sariang District, Mae Hong Son Province. Ten samples included the abbot, monks, community leader, teacher and residents of Pgaz-koen-yau Community in Ban Mae KaNai, Mae Ho Sub-District, Mae Sariang District, Mae Hong Son Province. Data were collected by interviewed and the descriptive analysis was used to analyze data in order to present quantitative descriptions of the data. The research found that 1) temples, schools and communities have supported the Buddhist activities and the traditional beliefs have conformed to Buddhist teaching. This has encouraged people in the community to observe the five precepts; 2) observance of the five precepts has created the happy and harmonious community with generous people and the villagers have engaged in the community activates; 3) village community should be set up and adults should be the good role models for the youngsters.